Changes in shoulder outcomes using ultrasonographic assessment of breast cancer survivors: a prospective longitudinal study with 6-month follow-up - Paula Gala-Alarcón (Nature Portfolio, 2021)
Abstract This study aimed to describe changes in supraspinatus tendon thickness, acromiohumeral distance, and the presence of fluid in the subacromial bursa as measured by ultrasound, as well as shoulder range of motion and strength, perceived shoulder disability, and health-related quality of life in women before and after breast cancer treatment. Women who underwent surgery for unilateral breast cancer who did not suffer from shoulder pain or difficulty performing activities of daily living in the 6 months prior to surgery were included. One pre-surgical (A0) and three post-surgical assessments at 7–10 days (A1), 3 months (A2), and 6 months (A3) after surgery were carried out. The thickness of the supraspinatus tendon on the affected side decreased between post-surgical (A1) and 6-month (A3) follow-up assessments (p = 0.029), although the minimal detectable change was not reached. The active range of motion of the affected shoulder decreased after surgery. Strength changes were observed in both shoulders after surgery. The intensity of shoulder pain increased between post-surgical and 6-month follow-up assessments. Shoulder function was decreased at the post-surgical assessment and increased throughout the follow-ups. Health-related quality of life declined after surgery. A trend of decreasing thickness of the supraspinatus tendon of the affected shoulder was observed. Detecting these possible structural changes early would allow for early or preventive treatment.